Karakter Fisiologi dan Hasil dari Tanaman Ciplukan (Physalis angulata) Pada Perlakuan Pemupukan Fosfat dan Mikoriza - Nila Wahyunita; Okti Herliana; Ahmad Fauzi; Rosi Widarawati (Jurnal Ilmu Pertanian Indonesia, 2021)
This study aimed to determine phosphate fertilizer and mycorrhiza dosages as well as the interaction of both treatments to the physiological character and the yield of ciplukan plants. The experiment was carried out from February to July 2020 on an experimental farm. The study used a Randomized Completely Block Design, consisted of two factors. The first factor was the dose of SP-36 fertilizer, containing 36% phosphate (P2O5), and the levels were P0 = 0% dose (0 kg/ha), P1 = 25% dose (75 kg/ha), P2 = 50% dose (150 kg/ha), and P3 = 100% dose (300 kg/ha). The second factor was the mycorrhizal dose, namely M0 = 0 g, M1 = 3 g, M2 = 6 g, and M3 = 9 g (containing 10 spores per 3 g). Each treatment combination was in triplicates. The measurement and observation data were analyzed using the analysis of variance (F-test), followed by Duncan's multiple range test with P-value = 0.05 and regression. The results showed that application of 75 kg/ha dose was equivalent to the application of 300 kg/ha. P uptakes at 75 kg/ha and 300 kg/ha dose of fertilizer were 22,03 ppm and 23,18 ppm, respectively. The plant growth rate was 12,39 g/cm2/week on the application of 75 kg/ha fertilizer and resulted in 14,24 g/cm2/week on 300 kg/ha dose. The mycorrhiza application was significantly different from the root infection at a dose of 6 g, namely 49.177%. There was an interaction between the dose of SP-36 fertilizer and the mycorrhiza on leaf chlorophyll content at a dose of 0% and 3 g mycorrhiza. Keywords: Physalis angulata, mychorrhiza, phospate fertilizer, physiological character and yield